Color matching of full ceramic versus metal-ceramic crowns - a spectrophotometric study - Greța, Delia Cristina; Gasparik, Cristina; Colosi, Horațiu Alexandru; Dudea, Diana (Medicine and Pharmacy Reports, 2019)
Background and aims. To verify the color match of metal-ceramic and full ceramic crowns, using instrumental methods. Methods. A number of 153 teeth (anterior and posterior teeth), in 62 patients, were restored with metal ceramic (MC, n=119), pressed-ceramic (PC, n=28), and zirconia-ceramic (ZC, n=6) full coverage crowns. The shade of a reference natural tooth was recorded instrumentally with a dental spectrophotometer (Vitaeasyshade Advance 4.0) in “single tooth measurement”, which provided the base color in Vita Classic (VC) and Vita 3D Master shades (3D). For verifying the outcome of the restoration “verify restoration” mode was used, and ΔE values were recorded for both VC and 3D Master shade guides. Moreover, matching symbols were also recorded (***=good, **=fair, *=poor). Descriptive statistics was performed and data were analyzed (One-sample z-Test, α=0.05) for comparison with visual thresholds in dentistry (Perceptibility Threshold – PT=1.2 and Acceptability Threshold – AT=2.7). Results. The data did not follow a normal distribution (Kolmogorov-Smirnov test, p<0.05). Recorded color difference was significantly higher than PT and AT, for all types of restorations, regardless of the coding system (p<0.05). For MC crowns in 2.52% (4.20% for 3D) of the cases the color difference was smaller than PT, in 19.32% (the same for 3D) of cases was between PT and AT, and in 78.15% (76.47% for 3D) of cases was higher than the AT. For PC crowns in 3.57% (0% for 3D) of the cases the color difference was smaller than PT, in 25% (32.14% for 3D) of cases was between PT and AT, and in 71.42% (67.85% for 3D) of cases was higher than the AT. In the case of ZC crowns none of the restorations had color difference smaller than PT, but in 16.66% of cases was between PT and AT, and in 83.33% of cases was higher than the AT, for both VC and 3D. Conclusion. Within the limitations of the study, a better color match was achieved in the case of pressed ceramic crowns, made of lithium disilicate. In most of the situations the color difference between the restoration and the reference tooth exceeded the perceptibility thresholds, but the matching was recorded as “fair” by the spectrophotometer.